Integrated approach for the bucking and production planning problems in forest industry - Vanzetti, Nicolás Andrés (2019)
Fil: Vanzetti, Nicolás Andrés. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Desarrollo y Diseño; Argentina.